Biofunctionalized PEDOT-coated microfibers for the treatment of spinal cord injury. (May 2016) - Alves-Sampaio, Alexandra; García-Rama, Concepción; Collazos-Castro, Jorge E.
Abstract: Poly(3, 4-ethylenedioxythiophene)-coated carbon microfibers (PEDOT-MFs) hold promise for developing advanced neuroprostheses and neural repair devices. We investigated the chronic cellular responses to PEDOT-MFs implanted into the uninjured and the transected rat spinal cord, and compared the effects of polymer surface biofunctionalization with covalently attached polylysine (PLL) or a multimolecular complex of PLL, heparin, basic fibroblast growth factor (bFGF), and fibronectin. An alginate gel was used to facilitate microfiber implantation and reduce connective tissue scarring after spinal cord injury (SCI). PLL/heparin/bFGF/fibronectin-functionalized PEDOT-MFs showed excellent integration within the uninjured and injured spinal cord, frequently establishing contact with neuronal somas, axons, dendrites and glial cells, accompanied by very little or absent scarring response. On the contrary, non-functionalized and PLL-functionalized microfibers provoked inflammation and fibrosis with loss of neural elements in the surrounding tissue. Within the lesion, the PEDOT-MFs by themselves facilitated longitudinal alignment of migratory cells and growing axons, and their modification with PLL/heparin/bFGF/fibronectin promoted tissue healing, enhancing blood vessel formation and axonal regeneration without increasing inflammation. These results support the incorporation of biofunctionalized electroconducting microfibers in neuro–electronic interfaces and lesion-bridging systems for the treatment of SCI.